Indonesia’s Role as A Cyber Protector in the Southeast Asia Region - Heryadi, Dudy; Rizaldi, Robby; Rahmadhani, Tia Panca; Miranti, Feby Diah; Juliastica, Febyanti (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
The rapid development of technology has finally opened up a new space that is connected through the internet. Southeast Asia is one of the regions with the highest percentage of internet users in the world. However, with this rapid digital growth, a new problem emerged. Cyberattacks that occurred in the Southeast Asia region caused a lot of data theft and failures in cyberspace systems in this region. Indonesia as chairman of ASEAN able to take advantage of the opportunity to handle the problem of cyberattacks in Southeast Asia. Therefore, this article discusses Indonesia’s role in dealing with cyber security problems in Southeast Asia through Indonesia’s role approach to Ego’s Role Conception and Alter’s Prescription. The research method used in this article is qualitative to explain Indonesia’s role in mitigating cyber security problems in Southeast Asia. By using Systematic Review with Preferred Reporting Items for Systematic Reviews and Meta-analyses as a reference in conducting literature studies. The research results show that Indonesia can be a cyber protector in Southeast Asia in line with strengthened organizational structures, diplomacy with partner countries, and cooperation between agencies with an interest in cyber protection.